2012
DOI: 10.4049/jimmunol.1100631
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Type I IFN Is a Physiological Immune Reaction to Apoptotic Cell-Derived Membrane Microparticles

Abstract: Membrane microparticles (MMP) released from apoptotic cells deliver signals that secure the anti-inflammatory response beyond the nearest proximity of the apoptotic cell. Plasmacytoid dendritic cells (pDC) are sentinels prepared to detect cellular processes that endanger the organism. They play a key role in the regulation of both pro- and anti-inflammatory immune responses. Based on the assumption that pDC could participate in the initiation of the anti-inflammatory response to apoptotic cells, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 74 publications
1
60
0
Order By: Relevance
“…During the past years, blockage of IFN-α has therefore been focus of pharmacological research (Petri et al, 2013). Only recently, our group was able to prove a direct link between the release of AdMPs and IFN-α secretion, showing that AdMPs can trigger the secretion of IFN-α from plasmacytoid dendritic cells (Schiller et al, 2012). These data provide a further link between AdMPs and characteristic features of SLE.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…During the past years, blockage of IFN-α has therefore been focus of pharmacological research (Petri et al, 2013). Only recently, our group was able to prove a direct link between the release of AdMPs and IFN-α secretion, showing that AdMPs can trigger the secretion of IFN-α from plasmacytoid dendritic cells (Schiller et al, 2012). These data provide a further link between AdMPs and characteristic features of SLE.…”
Section: Introductionmentioning
confidence: 71%
“…In this context, it has been shown that autoantigens accumulate within AdMPs after induction of apoptosis (Schiller et al, 2008). Furthermore, AdMPs have been shown to modulate the function of plasmacytoid dendritic cells (the main producers of IFN-α) as well as myeloid dendritic cells (Fehr et al, 2013;Schiller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, stimulation of pDC may have different outcomes. Thus activation of pDCs through TLR9 is reported to be a normal, physiological response to DNA released in membrane microparticles from apoptotic cells (1553). CpG ODNs able to activate Th1 responses in some settings may also promote immune tolerance through Treg with enhanced IL-10 production in other contexts (541,2122).…”
Section: Neutrophils May Interact With Plasmacytoid Dcs To Enhance Atmentioning
confidence: 99%
“…5B). In addition to protein components, T-MPs also contain RNAs (21,22) that are capable of stimulating DCs through the IFN pathway (23). To determine this possibility, we knocked down RIG-I, a key sensor for RNAmediated type I IFN production, using specific siRNA during the incubation of DCs with T-MPs.…”
Section: T-mps Activate Dcs Via Cgas-sting Pathwaymentioning
confidence: 99%